Literasi Teknologi sebagai Enabler Transformasi Digital dan CRM: Systematic Literature Review - Wulan Siti Nurjanah; Ade Sobandi; Fahmi Jahidah Islamy (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2026)
Digital transformation is a strategic agenda that cannot be avoided by modern organizations, but the failure rate of its implementation remains high due to insufficient human resource technology literacy. This research aims to: (1) synthesize empirical evidence on the role of technology literacy as an enabler of digital transformation; (2) analyze the determinants of success in digital CRM implementation; and (3) develop an integrated conceptual model that connects the three constructs. The method used is Systematic Literature Review (SLR) with PRISMA 2020 guidelines. Searches were conducted on Google Scholar using Boolean strings with filters for 2019–2024, yielding 2,467 articles. After a rigorous selection process, 18 final articles were analyzed using thematic synthesis. The results of the study identified five main themes: (1) technology literacy as an enabler of DT; (2) the digital capabilities of the organization; (3) digital CRM as a DT outcome; (4) the trilateral relationship of the third construct; and (5) the Indonesian and Southeast Asian contexts. This study proposes a three-level conceptual model: Technology literacy Foundation, Organizational Digital Transformation Capacity, Digital CRM Implementation Success. These findings provide theoretical contributions in the form of an integration framework for the three constructs that have been studied separately, as well as practical implications for HR managers and CIOs in designing CRM-based digital transformation strategies.